Dog breeds acquisition and owners’ awareness of associated surgical conditions in Nigeria (2018)
The study evaluated dog owners’ awareness of breed-associated surgical conditions in Nigeria as indices for breed choice with structured pre-tested questionnaires administered to dog owners in 17 states of Nigeria. Alsatians (36.8%) and Rottweiler (13%) breeds were mostly possessed by owners. The majority of the respondents were females (60.4%) owners. Lagos (53.4%) and Oyo (52.1%) states had the highest number of respondents while Kaduna (1.25%), Enugu (1.25%), Ekiti (1.25%), and Plateau (1.25%) states had the lowest. Most of the respondents (84.8%) are within the age bracket of 16 to 30 years, while 46.6% were University graduates and 90.8% had kept dogs previously. Factors that influenced dogs’ breed choices included: Body size (66.6%), coat colour (78.6%), natural intelligence (96.4%), information on the internet about the breed (54.6%), breed type possession by a close relative (53.4%), information regarding animal care from the Veterinarian (39. 2%), and recommendation by friends (42.6%). Respondents routinely visited the veterinary health centre for a general check-up and disease prevention (79.6%), vaccination and routine worming (79.2%), and treatment of diseases (79.8%). Respondents had varying knowledge of common surgical diseases: Cruciate ligament rupture (13.6%), gastric dilation/volvulus (13.6%), portosystemic shunt (15.0%), entropion (17.7%), ectropion (17.7%), osteochondrosis dessicans (17.7%), tracheal collapse (17.7%) etc. Only 10.9% of the respondents were aware of persistent health challenges in their dogs, while 84.4% of the respondents were uninformed of their dog breed predisposition to certain health challenges, and 82.3% of respondents were not aware of their dogs’ predisposition to any surgical disease. These findings imply a need for veterinarians’ input in dog choices, for recommendation of legislation mandating potential owners to seek out information about health care conditions of prospective dog breeds from authorized sources before possession to forestall frustrations, and avoidance of ultimate pet abandonment associated with management cost and social adjustment following surgical diseases